circDENND1B Participates in the Antiatherosclerotic Effect of IL-1β Monoclonal Antibody in Mouse by Promoting Cholesterol Efflux via miR-17-5p/Abca1 Axis - Xu, Fei; Shen, Li; Chen, Han; Wang, Rui; Zang, Tongtong; Qian, Juying; Ge, Junbo (Frontiers in Cell and Developmental Biology, 2021)
Inflammation is a crucial mediator of atherosclerosis, and several therapeutic methods that focus on inflammatory cytokines, including interleukin-1β (IL-1β), have proven effective in preventing atherogenesis. Circular RNAs (circRNAs) are a subclass of non-coding RNAs (ncRNAs) that can exert critical functions in the regulation of atherosclerosis. Here, using circRNA sequencing, we revealed that circRNA circDENND1B (mmu_circ_0000081) is a promising novel mediator of atherosclerosis in mouse. The expression of circDENND1B is negatively related to the progression of atherosclerosis and foam cell formation, and the upregulation of circDENND1B significantly alleviates foam cell formation induced by ox-LDL by promoting cholesterol efflux. Moreover, circDENND1B participates in the anti-atherosclerotic effect of IL-1β monoclonal antibody (IL-1β mAb), both in vivo and in vitro. With bioinformatic prediction and RNA pull-down assays, we determined that circDENND1B sponges mmu-miR-17-5p to promote Abca1 expression in cells treated with IL-1β mAb. Our study revealed that circDENND1B, a novel regulator of cholesterol efflux, is a potential therapeutic target in atherosclerosis and provides new insights into the interaction between inflammation and cholesterol transport.